Graptolite biozones of the Bohemian Lower and Middle Ordovician and their historical development - Kraft,J.; Kraft,P. (Journal of the Czech Geological Society, 1999)
An overview on graptolite zones in the Prague Basin is done. As the rests of graptolites are preserved nearly exclusively in the clayey shale facies of the Klabava, Sarka and Dobrotiva Formations, a reasonable graptolite zonation is establish only in there. Revised biostratigraphical scheme is proposed for this part of the Bohemian Ordovician. Only two zones are distinguished inside the Sarka Formation. No subzones are recommended to be used in all units. Characteristics of every unit cover its definition, history, list of graptolite species and important localities.
Keywords: biostratigraphy; graptolites; Ordovician; Prague Basin; historical development